Pengembangan Modul Pembelajaran Kimia Berbentuk Komik Berbasis Augmented Reality pada Materi Pokok Ikatan Kimia - Agussalim, Hastuti; Muharram, Muharram; Danial, Muhammad (Chemistry Education Review (CER), 2021)
This study is a development research that aims to develop and produce learning module in the form of comics based on augmented reality in Chemical Bonds learning subject. The development model used in the study refers to the 4D development model by Thiagarajan et al. The limited trial of this learning module was conducted at UPT SMAN 11 Pinrang. The results of the study reveal that (1) the development process of learning module employed the 4-D model which included 4 stages, namely (a) defining (define), (b) design, (c) development (develop), and (d) disseminating (disseminate), (2) the learning module is valid, effective, and practical. The validity of the module by the material experts obtained moderate validity and by the media experts obtained high validity categories. Limited field trials to 33 students of class X MIPA 1 obtained 81% class completeness after using the module. The learning motivation after using the module obtained an average score of 86 which was higher than before using the module which was 75. The effectiveness of learning module was also obtained by comparing the learning motivation of students based on the paired sample t-test with a significance p value smaller than α (0.00 < 0.05). The responses of students and teachers to the learning module developed also obtained a very practical category so that the media is confirmed to be practical.